NETRALISASI AIR LINDI RESIDU BAUKSIT (RED MUD) DENGAN MENGGUNAKAN AIR GAMBUT - Maya Santi (Universitas PGRI Semarang, 2018)
Bauxite residue or red mud is waste (by-products) generated from alumina processing. Some things are still the world's environmental issues, with respect to the red mud is in terms of the amount produced lots, as well as the properties of alkalinity and concentrations of Na relatively high. Na concentration and alkalinity of the red mud, is considered important to note because it gives a good effect in the short term and long term. In the short term, high solubility Na affect the quality of the leachate red mud and the long-term deals in terms of utilization and reclamation. One of the treatments that can be done to overcome the quality of red mud leachate is neutralization using peat water. The volume of peat water required to neutralize leachate red mud up to pH 7 is 1: 300. The percentage reduction in the concentration of Na in the red mud leachate after neutralization 99.5%.